Effect of Lysozyme on Resting Spores of Bacillus Megaterium - Suzuki, Yahiko (1969)
Resting spores of Bacillus megaterium ATCC 9885 were found to be markedly affected by lysozyme. Exposure to as little as 1.5 μg of lysozyme per ml caused the spores to lose refractility, the darkened spores to shed their coat structures, and the spore central bodies to lyse. The spores of seven other strains of B. megaterium and seven other Bacillus species were not similarly affected by lysozyme. Proteolytic enzymes such as pronase, trypsin, pepsin, and subtilisin did not induce the change. The action of lysozyme differed in certain important respects from that of common “physiological” germinants. Its action was considered to be direct via its enzymatic attack on exposed sites directly accessible in the resting spores of B. megaterium ATCC 9885.